2019
DOI: 10.1029/2019jc015124
|View full text |Cite
|
Sign up to set email alerts
|

Meridional and Zonal Eddy‐Induced Heat and Salt Transport in the Bay of Bengal and Their Seasonal Modulation

Abstract: This study investigates basin and regional-scale eddy (turbulent)-induced heat and salt transport associated with mesoscale eddies of the Bay of Bengal (BOB). A high level of eddy-induced transport is found in four subregions: the western boundary of the northern BOB (NB), the western BOB (WB), the southwestern BOB near Sri Lanka (SWB), and the southeastern BOB (SEB). The main seasons for eddy-induced heat transport in the NB and SWB are identified as the presummer (March to April) and summer monsoon (May to S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
9
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 46 publications
(99 reference statements)
4
9
1
Order By: Relevance
“…In the multi-year average EKE distribution map presented in Figure 4a, it can be observed that on the BOB west coast, central and western parts of the Andaman Sea, and southeast of Sri Lanka, EKE reaches a maximum of 2500 cm 2 /s 2 . Excluding the north BOB enclosed by 15-20°N, 91-95°E, high EKE values are restricted along the continental shelf, due to the presence of the EICC, consistent with previous observations [23,44]. Through reference to Figure 2a,b, it can be shown that seasonal circulation is, to a certain degree, correlated with EKE distribution as areas defined by strong current velocities are also characterized by high EKE values.…”
Section: Eddy Statistical Analysissupporting
confidence: 89%
See 1 more Smart Citation
“…In the multi-year average EKE distribution map presented in Figure 4a, it can be observed that on the BOB west coast, central and western parts of the Andaman Sea, and southeast of Sri Lanka, EKE reaches a maximum of 2500 cm 2 /s 2 . Excluding the north BOB enclosed by 15-20°N, 91-95°E, high EKE values are restricted along the continental shelf, due to the presence of the EICC, consistent with previous observations [23,44]. Through reference to Figure 2a,b, it can be shown that seasonal circulation is, to a certain degree, correlated with EKE distribution as areas defined by strong current velocities are also characterized by high EKE values.…”
Section: Eddy Statistical Analysissupporting
confidence: 89%
“…Results show that eddy-induced Ekman suction would cause Chl-a concentrations within the eddy to increase. Gonaduwage et al [44] find that baroclinic instability is the main mechanism that causes eddy transport, and to some extent, local wind stress and forcing from the equator also contribute to the seasonal modulation of eddy heat transfer. Simultaneously, transport of nutrients from the seabed, submesoscale movements, and internal waves leading to isobaric lines, can all affect changes in Chl-a.…”
Section: Chl Ringsmentioning
confidence: 99%
“…The seasonal MWT of all eddies in the whole bay is small, except for the southward extreme of 1.6×10 3 m 3 •s -1 in winter. These results of eddy-induced heat-salt transport in the Bay of Bengal based on measured temperature and salt data are different to the results obtained through theoretical calculation byGonaduwage et al (2019). The findings show that diverse seasonal changes of temperature and salinity in the Bay of Bengal might cause substantial deviation in eddy-induced heat/salt transport estimated theoretically.…”
contrasting
confidence: 87%
“…The heat and salt transport efficiencies of mesoscale eddies are related closely to eddy propagation speed (Dong et al, 2014;Gonaduwage et al, 2019;Stammer, 1998). In order to study the propagation direction and speed of mesoscale eddies in the Bay of Bengal, all eddy trajectories with lifetime ≥30 days from daily SLA fields are analyzed here.…”
Section: Seasonal Spatial Distribution Of Eddiesmentioning
confidence: 99%
“…Mathur et al (2019) studied the impact of freshwater advective stirring, pointing to implications for "the generation and/or evolution of frontal features in various quantities as the sea surface temperature, chlorophyll, biological activity, eddy kinetic energy and mixing rates in different parts of the ocean." Gonaduwage et al (2019) highlighted how "insight on the spatial distribution and temporal variability of the eddy-induced heat and salt transport in the BoB remains ambiguous." In this study, we explore the relative importance of horizontal freshwater volume flux, as a function of latitude, depth, and season, within the central axis of the BoB (Fig.…”
Section: Introductionmentioning
confidence: 99%